Probiotic Bifidobacterium bifidum G9‐1 ameliorates phytohemagglutinin‐induced diarrhea caused by intestinal dysbiosis. (9th October 2019) - Makizaki, Yutaka; Maeda, Ayako; Oikawa, Yosuke; Tamura, Saya; Tanaka, Yoshiki; Nakajima, Shunji; Ohno, Hiroshi; Yamamura, Hideki
Abstract: Diarrhea is largely caused by dysbiosis accompanying the hyperproliferation of Escherichia coli ( E. coli ). While current treatments can resolve the symptoms, they cannot suppress the proliferation of pathogenic bacteria in the intestine. Probiotics have numerous beneficial effects on host health, including restoring the balance of the intestinal microbiota. This study investigated the effect of the probiotic Bifidobacterium bifidum G9‐1 (BBG9‐1), which is active in intestinal dysbiosis, in the incidence of diarrhea, in the composition of the intestinal microbiota, and in the intestinal tissue of a rat model of phytohemagglutinin (PHA)‐induced diarrhea. The rats were treated with PHA, with and without BBG9‐1, and the microbiota composition throughout the intestine and stool was examined using high‐throughput 16S rRNA sequencing. In line with previous reports, PHA administration caused diarrhea as well as dysbiosis due to E. coli hyperproliferation. Histological findings indicated that the jejunal villus length was shortened. Rats that received BBG9‐1 showed clear improvements in dysbiosis, diarrhea symptoms, and jejunal villus length. Principal coordinates analysis demonstrated the microbiota profile to be more similar between the BBG9‐1 and normal groups than between the PHA and normal groups. These results indicated that BBG9‐1 suppresses the hyperproliferation of E. coli and restores the jejunal villus length, thereby improving dysbiosis, and in turn, alleviating the symptoms of diarrhea.